Low carbon readiness in social context: Introducing the social context of environmental identity model. Issue 2 (10th January 2021) - Kashima, Yoshihisa; O'Brien, Léan; McNeill, Ilona; Ambrose, Michael; Bruce, Gordana; Critchley, Christine R.; Dudgeon, Paul; Newton, Peter; Robins, Garry
Abstract : Low carbon readiness (LCR) is an aspect of environmental identity, an individual citizen's willingness to reduce carbon emissions and transition to low carbon lifestyle as a personal striving . Nevertheless, individuals' personal strivings are strongly influenced by the social context in which they are situated. We propose the social context of environmental identity model, which postulates that social contexts for LCR have a nested structure. The micro‐level Home is linked with other households through social networks at the meso‐level Community, which are further embedded in a macro‐level Society . These contexts are likely to influence LCR through different mechanisms. Home can exert direct influences by monitoring and reminding each other of the need to engage in low carbon behaviours. Community affects individuals' readiness by providing social capital. The macro‐level Society exerts social influence through societal norms not only its current descriptive norm but also through its dynamic norms about the changing trends into the future. We have tested and found support for these propositions in three national cross‐sectional data sets from Australia. Our discussions will centre around a need to investigate social and cultural processes involved in climate change mitigation, and to link these insights to public policies.